2012
DOI: 10.1029/2012ja017709
|View full text |Cite
|
Sign up to set email alerts
|

Detection of ionospheric Alfvén resonator signatures in the equatorial ionosphere

Abstract: .[1] The ionosphere response resulting from minimum solar activity during cycle 23/24 was unusual and offered unique opportunities for investigating space weather in the near-Earth environment. We report ultra low frequency electric field signatures related to the ionospheric Alfvén resonator detected by the Communications/Navigation Outage Forecasting System (C/NOFS) satellite in the equatorial region. These signatures are used to constrain ionospheric empirical models and offer a new approach for monitoring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 49 publications
3
20
1
Order By: Relevance
“…However, neither C/NOFS nor Chibis-M have revealed any signatures of continuous long-term ULF activity in the IAR band. Though electric field measurements onboard the C/NOFS satellite at near-equatorial latitudes revealed rare signatures near the terminator resembling the IAR multi-band spectral structure (Simões et al, 2012b), the frequencies of these structures were at least 5 times higher than model predictions. Therefore, an interpretation of these findings on the basis of the standard IAR model demands an unusually low plasma density in the upper ionosphere, more than an order of magnitude, as compared with existing ionospheric models.…”
Section: Inference For the Iar Excitation Mechanismmentioning
confidence: 83%
See 2 more Smart Citations
“…However, neither C/NOFS nor Chibis-M have revealed any signatures of continuous long-term ULF activity in the IAR band. Though electric field measurements onboard the C/NOFS satellite at near-equatorial latitudes revealed rare signatures near the terminator resembling the IAR multi-band spectral structure (Simões et al, 2012b), the frequencies of these structures were at least 5 times higher than model predictions. Therefore, an interpretation of these findings on the basis of the standard IAR model demands an unusually low plasma density in the upper ionosphere, more than an order of magnitude, as compared with existing ionospheric models.…”
Section: Inference For the Iar Excitation Mechanismmentioning
confidence: 83%
“…Thus, an interpretation on the basis of a standard IAR model demands unusually low plasma density in the upper ionosphere, more than an order of magnitude, as compared with existing ionospheric models (e.g., IRI). In our opinion, the fingerprint emissions found by Simões et al (2012b) are previously unknown spectral structures, but they cannot be interpreted as standard IAR signatures. Dudkin et al (2014) using the electric field sensor onboard the Chibis-M microsatellite found in the upper ionosphere only few events with signatures of the triggered excitation of the IAR.…”
Section: Introduction: Ulf Resonators and Waveguides In The Terrestrimentioning
confidence: 95%
See 1 more Smart Citation
“…Additionally, these results are important for the modeling of electromagnetic phenomena that rely on the shape of the ionospheric profile, including Schumann resonances, which occur in the cavity between the surface of the earth and the bottom side ionosphere (Simões et al, 2011), and the Ionospheric Alfvén Resonator (IAR), which occurs in the F-layer itself (Simões et al, 2012). Both of these phenomena have been observed by VEFI during the extreme solar minimum and are under consideration as possible metrics for future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Any approach to the interpretation of ionosphere resonance features demands a knowledge of spectral and dissipative properties of the IAR. Moreover, the sensitivity of modern electric field sensors and magnetometers onboard low-orbiting satellites became high enough to detect the IAR signatures in the top-side ionosphere (Simões et al 2012;Dudkin et al 2014). To interpret correctly the satellite observations an adequate model of the IAR eigenmode altitude structure is necessary.…”
mentioning
confidence: 99%